Manajemen Perguruan Tinggi Keagamaan Islam Di Era Revolusi Industri - almuarif, almuarif; Iqbal, Muhamad; Hadi, Akmal; Iswantir (Akademika : Jurnal Keagamaan dan Pendidikan, 2023)
In an effort to reconstruct and reposition Islamic Religious Higher Education (PTKI) in this modern era, it is important to change our perspective and increase awareness of the true role of Islamic education. This is not only related to the ability of each PTKI to compete with leading universities in the world, but also about a greater responsibility, namely fighting for Islamic values in the context of national life. Apart from producing intellectually competent graduates, PTKI is also responsible for forming noble characters. This research uses the "Library Research" method with a focus on text literacy and field phenomena. Data was collected through literature studies from books and journals relevant to the research topic. Research findings show that in the planning stage, several policies are needed, including structuring, controlling and strengthening institutions; academic standardization; improving the quality and welfare of lecturers; development of academic and student programs; development of employment programs; and optimizing mentoring programs. In implementing quality management, development strategies need to be built, stakeholder trust and confidence must be created, centers of competitive advantage need to be built, information and communication technology needs to be developed, professionalism needs to be increased, quality must be guaranteed, good relations with stakeholders must be maintained, cooperation with other institutions needs to be built, and commitment to the Islamization of academia must be developed